PENGEMBANGAN MEDIA ABC (AYO BELAJAR CERIA) BERBASIS LITERASI DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SD INPRES MANGASA I - Astri Nurmala Taha; Muhammad Akhir; Andi Paida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a develolopment research that aims to produce ABC (Ayo Belajar Ceria) learning media in Indonesian subjects to increase the learning interest of class V students of SD Inpres Mangasa 1. The development model used refers to 4D model which includes defne, design, develop and disseminate. The instruments used are validations sheets of questionnaires as well as documentation. The results of this study are first, the validity of ABC media based on media expert validation is 95% and 95.3% which can be categorized as very valid. Second, the practically of ABC learning media based on teacher and students response questionnaires obtained a very practical category. Third, the effectiveness of ABC learning media on students learninginterest using an independent t-test showed a significance value of 0.000 or a sig. value<0.05 so thatthere is a significant difference between learning interest in the control class and the experimental class before and after using ABC media. Thus, this folding confirms that ABC media can be used as an alternative in increasing student learning interest.